2005
DOI: 10.1021/jp044312q
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Length in a Fluid−Fluid Demixed Colloid−Polymer Mixture

Abstract: We report measurements of the interfacial profile close to a vertical wall in a fluid-fluid demixed colloidpolymer mixture. The profile is measured by means of laser scanning confocal microscopy. It is accurately described by the interplay between the Laplace and hydrostatic pressure and from this description the capillary length is obtained. For different statepoints approaching the critical point the capillary length varies from 50 to 5 µm. These results are compared to theory. The mass density difference ∆F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…Recently, it has been demonstrated that the depletion attraction between colloids and a hard wall can also lead to interesting wetting phenomena [17][18][19]. Experiments have shown that a wetting layer of the dense colloidal phase is usually present at the wall of the container [20,21]. The exceptional feature of phase-separated colloid-polymer mixtures is the ultralow interfacial tension between the liquid and gas phases [22 -24]: it can be a million times smaller than for a typical oil-water interface, thus making the thermal roughness of the interface a thousand times bigger.…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that the depletion attraction between colloids and a hard wall can also lead to interesting wetting phenomena [17][18][19]. Experiments have shown that a wetting layer of the dense colloidal phase is usually present at the wall of the container [20,21]. The exceptional feature of phase-separated colloid-polymer mixtures is the ultralow interfacial tension between the liquid and gas phases [22 -24]: it can be a million times smaller than for a typical oil-water interface, thus making the thermal roughness of the interface a thousand times bigger.…”
mentioning
confidence: 99%
“…Measurement of ultralow interfacial tensions is notoriously difficult. Many available techniques, such as drop shape [1] or interfacial profile analysis [2], rely on optical visualization. However, in weakly segregated and nearcritical systems, the optical contrast between the phases is generally small.…”
mentioning
confidence: 99%
“…Numerical domain is presented on the figure 2. This equivalent size is (1800x1800x600)µm 3 , that means water and oil inlet channel have a length of 600 µm, and the equivalent mesh size is (384x384x128). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An emulsion is defined as the temporarily stable dispersion of a liquid into another one that is not miscible [2]. When the scale of the liquid-liquid flow is smaller than its capillary length [3], interfacial tension dominates over shear stress and gravity [4], making the dispersion highly reproducible in slow conditions [5]. These slow conditions ensure a highly monodisperse emulsion [6], that is usually appropriate for targeted applications like microreaction synthesis [7].…”
Section: Introductionmentioning
confidence: 99%